The Analysis of Influence Factors and Solutions to the Lack of Sex Education for Minors in China from the Perspective of the Ecological Systems Theory - Zhang, Yutong (Transactions on Social Science, Education and Humanities Research, 2024)
Nowadays the implementation of sex education is still insufficient in China, although it has been improved gradually. This paper looks at the dilemma in sex education in modern society in China, which is mainly concerned with the tension between the lack of systematic education on sex at all ages and the need for teenagers to better protect themselves from danger. Actually, sex education is of great significance to help children cultivate a sense of identity and gender equality, consciously respect members of the opposite sex, establish a sense of self-protection, and confront the concept of sex correctly. However, as a result of cultural conservatism, few educational systems in China have a clear sense of sex in all aspects. The study reveals the influence factors on the lack of sex education for minors in China from the perspective of the ecological systems theory, pointing out the negative impact of its absence and potential solutions to relieve the tension. Influence factors include the historical legacy Impact of Cultural Conservatism and the lack of policy support for the sexual education of minors, which belong to the ecosystems, while the impact of social media belongs to the macro system.